2020
DOI: 10.1371/journal.pone.0235291
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and space-time clustering and demographic characteristics of human nontyphoidal Salmonella infections with major serotypes in Toronto, Canada

Abstract: Nontyphoidal Salmonella enterica (NTS) causes a substantial health burden to human populations in Canada and worldwide. Exposure sources and demographic factors vary by location and can therefore have a major impact on salmonellosis clustering. We evaluated major NTS serotypes:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
(63 reference statements)
0
22
0
Order By: Relevance
“…As demonstrated here and in several similar studies, the spatial scan statistic is useful for identifying epidemiologically relevant clusters of salmonellosis in space, time, and space-time (Graziani et al, 2015;Varga et al, 2015Varga et al, , 2020. It may be beneficial for local and provincial health authorities to incorporate spatial, space-time, and multi-focused cluster tests into existing practices for surveillance of enteric diseases such as Salmonella.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As demonstrated here and in several similar studies, the spatial scan statistic is useful for identifying epidemiologically relevant clusters of salmonellosis in space, time, and space-time (Graziani et al, 2015;Varga et al, 2015Varga et al, , 2020. It may be beneficial for local and provincial health authorities to incorporate spatial, space-time, and multi-focused cluster tests into existing practices for surveillance of enteric diseases such as Salmonella.…”
Section: Discussionmentioning
confidence: 69%
“…Depending on the model selected, researchers can control for the underlying population and various covariates such as age and sex. Previous studies in Ontario and elsewhere have demonstrated the utility of the spatial scan statistic for detecting spatial, temporal and space-time clusters of salmonellosis caused by several different serovars (Graziani et al, 2015;Varga et al, ,2015Varga et al, , , 2020. The spatial scan statistic and other statistical modelling techniques have also been useful in identifying risk factors associated with specific serotypes that may not have otherwise been identified via routine case investigation (Graziani et al, 2015;Simpson et al, 2019;Varga et al, 2015).…”
Section: Impactsmentioning
confidence: 99%
“…We calculated the relative risk (RR) for each FSA belonging to a significant spatial cluster to prevent the assumption of similarity of RRs of FSAs within a cluster (Desjardins et al, 2018;Varga et al, 2020). Statistically significant spatial high-rate STEC clusters and the RRs of FSAs included in significant clusters were illustrated in ArcGIS 10.7.1 (ESRI, Inc., Redlands, CA).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Spatial scan statistics have been used in public health research in Canada to identify high-infection rate areas. These include salmonellosis in Ontario (Varga et al, 2015(Varga et al, , 2020Paphitis et al, 2020); Campylobacter infections in Manitoba (Green et al, 2006); Campylobacter, E. coli, Salmonella, and Shigella infections in New Brunswick (Valcour et al, 2016); STEC O157 infections in Alberta (Pearl et al, 2006); and notifiable gastrointestinal illnesses in the Northwest Territories (Pardhan-Ali et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have specifically analyzed the impacts of hunter food safety procedures on the contamination of deer and moose carcasses [ 10 , 87 , 88 , 89 ]. Bacterial foodborne diseases are more common during the summer [ 90 , 91 , 92 ]. For example, in Europe, higher bacterial colony counts have been detected on game meat carcasses during the summer compared to the winter season [ 93 ].…”
Section: Overview Of Foodborne Diseasesmentioning
confidence: 99%